2007
DOI: 10.1111/j.1439-0523.2007.01280.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified synthetic varieties: a breeding method for forage crops to exploit specific combining ability

Abstract: Hybrid varieties have not become commercially successful in perennial and self-incompatible forage crops because of their severe inbreeding depression and/or ineffectiveness in commercial seed production. Here, a modified synthetic variety (MSV), a breeding method for forage crops is proposed, where specific combining ability (SCA) is exploited in a way different from that in hybrids. As Syn-l seeds from only two of its parental clones are used to produce its Syn-2, its performance in Syn-2 partially depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…1980), alfalfa (Gau et al . 1989) and timothy (Tamaki et al . 2007) have shown that not only GCA but also SCA effects exist in their yields, and that the scale of the latter effect is as large as that of the former in alfalfa and timothy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1980), alfalfa (Gau et al . 1989) and timothy (Tamaki et al . 2007) have shown that not only GCA but also SCA effects exist in their yields, and that the scale of the latter effect is as large as that of the former in alfalfa and timothy.…”
Section: Resultsmentioning
confidence: 99%
“…One of the major reasons for this slow yield increase in forage crops is that breeders still widely apply synthetic variety development or other methods whereby only general combining ability (GCA) is effectively exploited (Tamaki et al . 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of self‐incompatible forage crops, including timothy, often relies on the production of synthetic (Syn) varieties (Tamaki et al. ). A variety developed by Syn population development in self‐incompatible forage crops originated from intercrossing a limited number of non‐inbred parents possessing high general combining ability (GCA) for specific traits (Sleper and Poehlman ).…”
mentioning
confidence: 99%
“…; Tamaki et al . ). The risk of severe inbreeding depression in CSS could not be shown in our limited experiments, which were conducted for only one CSS strain in one location.…”
Section: Discussionmentioning
confidence: 97%